A Challenging Case of Oral Lichen Planus: A Comprehensive Review - V C Vinod; Roza Rajkumar Baviskar (Wolters Kluwer Medknow Publications, 2023)
Oral lichen planus (OLP) is a chronic mucocutaneous disorder affecting the oral mucosa. This case report presents a comprehensive assessment of a 64-year-old male patient with OLP, detailing the clinical presentation, diagnosis, and management. The patient's chief complaint was a persistent burning sensation in the oral cavity for several months. Furthermore, he expressed the need to replace missing teeth. The patient was treated with a combination of topical corticosteroids, multivitamins, and systemic steroids, which yielded significant improvement in symptoms. This case highlights the importance of early diagnosis and effective management of Oral Lichen Planus,emphasizing the need for proper understanding and treatment of this oral condition.